Derecho «canónico y litúrgico» en las «actas» de la redacción del Codex Iuris Canonici - Gandía Barber, Juan Damián (Ius canonicum, 2023)
In the drafting of the section on other acts of worship, and sacred places and times in the current Code, it was necessary to define and distinguish between canon and liturgical law in order to decide which canons were to be retained and which might be rewritten into the new text of the CIC. This paper explores the documents that deal with this subject, already known due to the publication of the proceedings, and presents fragments of other, previously unpublished documents, from the ‘minutes’ of the process stored in the archive of the Dicastery for Legislative Texts.